Innovative Technology Integration in Teaching Practicum: Pre-Service Teachers' Mastery of the TPACK Framework at Universitas Widya Gama Mahakam Samarinda - Heriyadi, Akhmad; Effendi Limbong; Iwan Setiawan (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2024)
Consider how Technology has been used in the teaching and learning process. This study aimed to explore PSTs' final practice in practicum integrated into Technology and how they solve the problem if they have it. This research was conducted at Widya Gama Mahakam University. This study focused on PSTs' competence when designing and using Technology in teaching final practice in practicum programs through the TPACK framework. The design of this study was a qualitative study that illustrates the PSTs' competence in integrating Technology in the final practice teaching in the practicum program through TPACK Framework. There were 22 PSTs of seven semesters as the participants. There were three items of instruments. Documents, interviews, Observation, and three PSTs were willing to be interviewees. The study result showed they plan the lesson well before teaching using Technology even though there are slight differences in their performance. The Technology they used, combined with pedagogy and content, varied depending on the state of equipment, facilities, PSTs' abilities, and student levels. PSTs also stated the involvement of supervising teachers was beneficial when they faced difficulties in teaching practice. The Researcher suggested that PSTs design their lesson plan effectively. The teacher preparation program prepares PSTs with technological education skills, and the school provides nondigital or digital technology support, student-centered software, and collaboration media tools.